Aging and Death in Edward Albee’s The Sandbox and Tennessee Williams’s The Milktrain Doesn’t Stop Here Anymore - Cristian, Réka M. (Hungarian Journal of English and American Studies, 2020)
With focus on the tropes of aging and death in Edward Albee’s The Sandbox (1960) and Tennessee Williams’s The Milktrain Doesn’t Stop Here Anymore (1963), the essay investigates the negotiation of the protagonists’ identity through specters of age and the means of encountering death, and it analyzes the representation of the dramas’ senior citizens with special regard to the ways in which these characters challenge mainstream cultural constructions of aging. On their deathbed, both Albee’s and Williams’s protagonists are reconnecting with their pasts in idiosyncratic ways: they build up a conscious “age autobiography” (Margaret Morgenroth Gulette) in an inventory of events and feelings assessing a complete(d) life and achieve an “agewise” (Gulette) identity that comes full circle in the very moment of grace. The characters who escort these two elderly women on their last journey reconceptualize the sense of intimacy between people. The dialogic potential of their empathy, care, and unconditional support during the end-game of the protagonists accommodates difference in various contexts by blurring the boundary between the old and the young as well as the one between men and women, because death has neither age nor gender. Thus, these intergenerational exchanges help elder characters’ agewise enterprises into the unknown gain a cathartic sense of freedom. (RMC)